Prevalence of left atrial appendage thrombus detected by transoesophageal echocardiography before catheter ablation of atrial fibrillation in patients anticoagulated with non-vitamin K antagonist oral anticoagulants. Issue 1 (11th June 2018) - Alqarawi, Wael; Birnie, David H; Spence, Stewart; Ramirez, F Daniel; Redpath, Calum J; Lemery, Robert; Nair, Girish M; Nery, Pablo B; Davis, Darryl R; Green, Martin S; Beauchesne, Luc; Chan, Kwan; et al.
Abstract: Aims: There is ongoing controversy about the need for routine transoesophageal echocardiography (TOE) prior to atrial fibrillation (AF) ablation. Recently, the debate was reignited by the publication of a large series of patients showing a prevalence of left atrial appendage thrombus (LAAT) on TOE of 4.4%. We sought to assess the prevalence of LAAT on TOE before AF ablation at our institution. Methods and results: Consecutive patients scheduled for AF ablation at our institution between January 2009 and December 2016 were included. All patients were on oral anticoagulation for at least 4 weeks prior to TOE. Transoesophageal echocardiographies were performed 3–5 days prior to scheduled AF ablation. Data were collected utilizing a prospective database. In all, 668 patients and 943 AF ablation procedures were included. Mean age was 64 ± 11 years, 72% were male, average CHADS2 score was 1.0 ± 1.0, and 72% of the patients had paroxysmal AF. At the time of ablation, 496 (53%) were on non-vitamin K antagonist oral anticoagulants (NOACs) and 447 (47%) were on Warfarin. There were three cases with LAAT (3/943, 0.3%), all of whom had persistent AF and were on Warfarin. Two patients underwent surgical ablation and the third patient did not undergo ablation. Conclusion: In our experience, the prevalence of LAAT in patients on anticoagulation therapy undergoing TOE before catheter ablation of AF is 0.3%, which was much lower than recently reported. None of the patients with paroxysmal AF or on NOACs were found to have LAAT. Rather than routine use of TOE prior to AF ablation, a risk-based approach should be considered.